Pengembangan Media Pembelajaran PJOK Berbasis Permainan “Parkour Kids” di Sekolah Dasar Fase A untuk Meningkatkan Kemampuan Motorik Kasar Siswa MI Islamiyah Babadan - Masrukhan, Ibnu; Utomo, Andy Widhiya Bayu; Septianingrum, Kartika (Jurnal Ilmiah Global Education, 2025)
This study aims to develop a Physical Education, Sports, and Health (PJOK) learning media based on the “Parkour Kids” game to improve the gross motor skills of elementary school phase A students at MI Islamiyah Babadan. The research employed a Research and Development (R&D) approach using the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The product was developed through needs analysis, material and media design, expert validation, and small- and large-scale trials. Data collection instruments included interviews, validation questionnaires from content and media experts, and student response questionnaires. The results indicated that the PJOK learning model based on the “Parkour Kids” game (including hurdle jumps, forward rolls, crawling under obstacles, walking on beams, zigzag running, running, and jumping) is considered feasible, enjoyable, safe, and effective in stimulating and enhancing students’ gross motor skills. The developed product is deemed practical and significantly improves PJOK learning outcomes for elementary school phase A students.